2019
DOI: 10.1364/ao.58.000250
|View full text |Cite
|
Sign up to set email alerts
|

Versatile photoacoustic spectrometer based on a mid-infrared pulsed optical parametric oscillator

Abstract: We demonstrate the usefulness of a nanosecond pulsed single-mode mid-infrared (MIR) optical parametric oscillator (OPO) for Photoacoustic (PA) spectroscopic measurements. The maximum wavelength ranges for the signal and idler are 1.4 µm to 1.7 µm and 2.8 µm to 4.6 µm, respectively, and with a MIR output power of up to 500 mW. Making the OPO useful for different spectroscopic PA trace-gas measurements targeting the major market opportunity of environmental monitoring and breath gas analysis. We perform spectros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…For highly sensitive and selective PAS measurements it is desirable to have a MIR light source with high power, fast wavelength sweeping and large wavelength tunability covering the 2.8 m to 4.4 m region, where most trace gasses have strong vibrational transitions. For this a nanosecond pulsed MIR-OPO is a good candidate, since it provides good molecular selectivity, due to large wavelength tunability, relative narrow linewidth, and high optical output powers [ 34 , 35 ]. The MIR-OPO used is based on a 30 × 20 × 1 mm periodically poled lithium niobate (PPLN) nonlinear crystal with a fanned-out structure of poling period ranging from 27.4 m to 31.75 m (HC Photonics).…”
Section: Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…For highly sensitive and selective PAS measurements it is desirable to have a MIR light source with high power, fast wavelength sweeping and large wavelength tunability covering the 2.8 m to 4.4 m region, where most trace gasses have strong vibrational transitions. For this a nanosecond pulsed MIR-OPO is a good candidate, since it provides good molecular selectivity, due to large wavelength tunability, relative narrow linewidth, and high optical output powers [ 34 , 35 ]. The MIR-OPO used is based on a 30 × 20 × 1 mm periodically poled lithium niobate (PPLN) nonlinear crystal with a fanned-out structure of poling period ranging from 27.4 m to 31.75 m (HC Photonics).…”
Section: Experimental Setupmentioning
confidence: 99%
“…This leads to a degraded spectral resolution of the QEPAS sensor, when performing measurements at fast spectral tuning rates. Consequently, when performing measurements on a complex gas mixture, where cross-interference effects are present, it becomes difficult, or almost impossible, to identify individual gases and quantify their concentrations [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lamard L et al demonstrated a single longitudinal mode pulsed OPO laser. 69 The OPO delivered an average power output of 345 mW, with continuous tunability in the range of 2.8-4.6 μm, which achieved spectroscopic analysis of CH 4 , NO 2 , and NH 3 with the resolution of 1.5 cm −1 . And the LODs of CH 4 and NO 2 was 8 ppb and 1.6 ppm (1σ).…”
Section: Multicomponent Gas Analysis Of Pas Systems Using Nonlinear L...mentioning
confidence: 99%
“…3 Mid-infrared laser sources have been used for PA detection of NO 2 . 4,5 Detection limit down to 0.5 ppb was reached with a quantum cascade laser emitting at the wavelength of the strong vibrational transitions of NO 2 around 6250 nm, 5 but laser sources at long wavelengths are often expensive and have limited wall-plug efficiencies in the order of a few percent. Fortunately, NO 2 absorbs strongly also in the visible wavelength range, where detection limits below 1 ppb have been demonstrated in PA measurements, with lasers as light sources.…”
mentioning
confidence: 99%
“…As opposed to most other sensing techniques based on optical absorption, PA detectors have great potential toward miniaturization because the PA signal is inversely proportional to the sample volume . Mid-infrared laser sources have been used for PA detection of NO 2 . , Detection limit down to 0.5 ppb was reached with a quantum cascade laser emitting at the wavelength of the strong vibrational transitions of NO 2 around 6250 nm, but laser sources at long wavelengths are often expensive and have limited wall-plug efficiencies in the order of a few percent. Fortunately, NO 2 absorbs strongly also in the visible wavelength range, where detection limits below 1 ppb have been demonstrated in PA measurements, with lasers as light sources. The high sensitivity is achieved using high-power lasers and resonant acoustic cells.…”
mentioning
confidence: 99%